2013
DOI: 10.1007/s12262-013-1021-2
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relation Between Pyloric Muscle Thickness and Clinical and Laboratory Data in Infants with Hypertrophic Pyloric Stenosis?

Abstract: Literature about the association between clinical and laboratory presentation and pyloric muscle thickness in infants with pyloric stenosis is lacking. The objective of this study is to examine the effect of pyloric muscle thickness on clinical and laboratory presentation in infants with pyloric stenosis. Thirty infants with hypertrophic pyloric stenosis presented at the Maternity and Children Hospital, AlMadinah, Saudi Arabia, were included in this study analysis. Clinical and laboratory data of these infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…4 Gastric outlet obstruction causes vomiting leading to electrolyte disturbances, dehydration, and failure to thrive. 5,6 The gold standard in treatment of IHPS consists of a longitudinal seromuscular incision along the entire length of the hypertrophic muscle resulting the unharmed mucosa to bulge through the incision. [7][8][9] Laparoscopic surgery was developed by Kurt Semm in the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…4 Gastric outlet obstruction causes vomiting leading to electrolyte disturbances, dehydration, and failure to thrive. 5,6 The gold standard in treatment of IHPS consists of a longitudinal seromuscular incision along the entire length of the hypertrophic muscle resulting the unharmed mucosa to bulge through the incision. [7][8][9] Laparoscopic surgery was developed by Kurt Semm in the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to recognize IHPS early and treat it accordingly with fluid resuscitation [ 18 ]. In previous studies, ultrasonographic detection of increased pyloric muscle thickness was found to be associated with biochemical parameters, including metabolic alkalosis [ 6 19 ]. This relationship may be explained by persistent vomiting caused by gastric outlet narrowing due to increased muscle thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Hypochloremia with metabolic alkalosis is a typical laboratory finding that results from the loss of gastric hydrochloric acid. A recent study reported a positive correlation between symptom duration and serum bicarbonate levels [ 5 ] and another study reported that pyloric muscle thickness is a significant factor for dehydration and high bicarbonate levels in infants with IHPS [ 6 ]. Normalization of metabolic derangement by fluid rehydration is important for avoiding complications after operation, such as apnea [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 The incidence of HPS is approximately 2 to 5 cases per 1000 live births, which is four times higher in male gender as compared to girls. [2][3][4] The other main clinical symptoms except vomiting included visible peristaltic waves and olive-shaped lumps and finally causes severe malnutrition and death. Therefore, for a better prognosis results, early treatment is required.…”
Section: Introductionmentioning
confidence: 99%